Persepsi Jamaah Wahdah Islamiyah terhadap Tradisi Pernikahan di Desa Beroanging Kabupaten Jeneponto - Riska Marsya; Darman Manda; Rasyid Ridha (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to analyze the tradition of marriage in Beroanging Village, Jeneponto Regency, the perception of Wahdah Islamiyah pilgrims towards the wedding tradition in Beroanging Village, Jeneponto Regency, and the dynamics of social conflicts that arise from the difference in views of Wahdah Islamiyah pilgrims and the community towards the wedding tradition in Beroanging Village, Jeneponto Regency. Using a qualitative approach in phenomenological research, the data collection techniques employed include observation, interviews, and documentation. The results of the study show that the wedding tradition in Beroanging Village has various special series on the day before simorong, including Ammuntuli Je'ne, Anggentung, Appassili, A’bu’bu, Ammuntuli Korongtigi, A’ratek, Anjama Leko', and Akkorongtigi. Each series of marriage traditions has a meaning and value. The Wahdah Islamiyah congregation interprets the marriage tradition as a custom carried out by the previous person, whether carried out or not, will not affect the validity of a marriage bond. The community and the Wahdah Islamiyah congregation in Beroanging Village, Jeneponto Regency have quite significant differences of opinion. The community considers that the tradition of marriage cannot be left alone, while the Wahdah Islamiyah congregation has the opposite opinion. These differences present social conflicts, even though the disputes that occur fall into the category of non-confrontational conflicts.